The need for financial education in the face of the social media and cryptocurrency phenomenon - Sonia Martin Gomez; Angel Bartolome Muñoz de Luna (Business, Management and Economics Engineering)
Purpose – is to provide evidence of how social networks act as an indispensable channel in the cryptocurrency phenomenon and its public perception, analysing the context in which it occurs, as well as the patterns followed and the most commonly used channels.